Pengaruh Program Membership dan Kualitas Layanan Perspektif Ekonomi Islam Terhadap Minat Pembeliaan Berulang Dengan Kepuasan Pelanggan Sebagai Variabel Intervening - Utomo, Ardiawan; Indriani, Farida (Jurnal Ilmiah Ekonomi Islam, 2024)
This research aims to find out, study and analyze the influence of membership programs and service quality on repeat purchase interest with customer satisfaction as an intervening variable. The population is Ngoembah laundry customers with a total of 600 customers. The number of samples for this research was 86 customers using the Slovin formula. Researchers use quantitative analysis to analyze data. To collect data directly from Ngoembah laundry customers, using a survey or questionnaire method was chosen. This research uses Structural Equation Modeling (SEM) which is a multivariate analysis method which combines factor analysis and regression analysis. The research results obtained show that the membership program has a positive and significant effect on customer satisfaction. Service quality has a positive and significant effect on customer satisfaction. The membership program has a positive and significant effect on repurchase interest. Service quality has a positive and significant effect on repurchase intention. Customer satisfaction has a positive and significant effect on repurchase intention.